Shakespeare murders - Gupta, Sharon (New Delhi Tara, 2017)
It s 1602 and William Shakespeare is at the height of his popularity. South of the River Thames in the borough of Southwark, the Globe playhouse dominates the skyline. The Chamberlain s Men, led by Richard Burbage, function there. Shakespeare is their in-house playwright. Burbage s acting prowess combined with Shakespeare s literary talent make the Globe the most successful theatre of its time.
Keywords: Civil servant as an author; Fiction - Crime